KONSTRUKSI BERITA MEDIA MASSA CNN (CABLE NEWS NETWORK) TERHADAP ISIS (ISLAMIC STATE OF IRAQ AND SYRIA) SEBAGAI TRANSNATIONAL ORGANIZED CRIME - Andrea Suci Varera; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
ISIS (Islamic State of Iraq and Syria) is one of a constantly reported troop in international mass media since 2014. CNN (Cable News Network) is a mass media that incessantly publish news coverage on ISIS. ISIS portrayed as new threat to the world as it is a transnational organized crime. News coverage on ISIS brought a certain identity to its. This research aims to describe how CNN international by it coverage portray ISIS as transnational organized crime.This research use Constructivism perspective, mass media's role theory and Agenda setting concept to analyze and describe itself. Content analysis and news context from CNN online news coverage will also be used in order to prove the hypothetical answer. Level of analysis in this research is in Agent and Structure level and focuses in describing CNN roles in ISIS coverage.Mass media's role and function in news coverage and in the world, ISIS development, and news construction from CNN to ISIS as a new threat to international security are described as well in this researach. Furthermore, it will describe few examples of ISIS news coverage influences, such as establishment of coalition, pact, and nation's foreign policy on ISIS.Keywords : Cable News Network, Islamic State of Iraq and Syria, Transnational organized crime, Agenda setting, News coverage